Theophylline versus NSAID in the Treatment of Postdural Puncture Headache in Obstetric Patients - Mehmood, Tariq; Khan, Rao Ali Shan; Qarni, Muhammad Awais; Khalid, Usman; Iftikhar, Hina (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the effectiveness of oral Theophylline compared to Non-Steroidal Anti-Inflammatory Drugs in the management of postdural puncture headache in obstetric patients.Study Design: Quasi-experimental Study.Place and Duration of Study: Anaesthesia Department, Combined Military Hospital, Kharian Pakistan, from Apr to Sep 2018.Methodology: Our study enrolled 60 pregnant women suffering from postdural puncture headache. The were divided in to two groups, NSAID-Group (Group-A) who received 30mg of Ketorolac in three divided doses in 24 hours and Theophylline- Group (Group-B) who received 750mg of oral Theophylline in three divided doses in 24 hours after which effects of both drugs were noted.Results: Pregnant women were enrolled in NSAID-Group and in Theophylline Group. Mean baseline Visual Analogue Scale score was 7.500±0.97 in NSAID-Group and 7.33±0.92 in Theophylline Group. Mean weight was 66.86±5.25 kg in NSAID-Group and 67.16±7.01 Kg in Theophylline-Group. In NSAID-Group efficacy was noted in 7(23.3%) patients as compared to 25(83.3%) patients in Theophylline-Group, (p